The risk of scaling in Danish geothermal plants and its effect on the reservoir properties predicted by hydrogeochemical modelling. (November 2022) - Kazmierczak, Jolanta; Marty, Nicolas; Weibel, Rikke; Nielsen, Lars Henrik; Holmslykke, Hanne Dahl
Highlights: Injectivity problems in Danish geothermal plants caused by scaling. Decrease in the reservoir porosity induced by mineral precipitation. Barite identified as a major precipitate in the near field of the injection wells. Negligible influence of carbonates and clay scales and barite nucleation in the geothermal loops. Abstract: Injectivity problems have been observed in two of three Danish geothermal plants. The utilized geothermal reservoirs comprise sandstones of Lower Triassic and Upper Triassic – Lower Jurassic. The great variations in the formation mineralogy and the chemical composition of their brines allow for a thorough analysis of the differences in the potential risks of scaling. The key scaling processes upon injection of the cooled brines into the reservoirs were identified and changes in the reservoir porosity assessed by hydrogeochemical modelling. Scaling was predicted to be of importance only in one of the geothermal reservoirs, where barite precipitation in the near field of the injection well was identified as a potential risk and could potentially alter the reservoir porosity. Scaling induced by barite nucleation in the injection well, and precipitation and dissolution of carbonates, silicates and clays in the geothermal reservoirs are all of minor importance.